The influencing factors of employee turnover intention in hotel industry in Ning Xia China - Huai, Yang (2015)
This research study about the most reason for quitting the job by exiting employees, work factors and its influence to employee turnover, the relationship between reasons for quitting the job and work factors and the relationship between demographic factors and reasons for quitting the job. In this study used 500 respondent of exiting employees. The tool of analyses used is correlation concept by Chi - Square test for testing of hypotheses. The results of this study are: the most reason for quitting the job is dissatisfaction with supervisor treatment (49.2%), it means in their company have poor relationship between the employees and managers. The second most frequent reason was salary (12%). This research found also that in term work factors, work environment are the highest level of agreement in all respondents. After that, supervision and communication are lower rated and similar in agreement. Job satisfaction was the lowest rated work factor. Thus, overall most of the employee who left tends to agree on the goodness of the work environment aspects. Most agreed that the work conditions are good and that adequate equipment was available. This study found that Chi - Square Test for all items of work factors are 0.001 (Assymp.Sig.2-sided) where it’s smaller than 0.05. It means there is relationship between the most frequent reason for quitting and work factors. This study found also that there is relationship between demographic factors and reasons for quitting the job. It seen from the result of Chi - Square Test for all items of demographic factors are 0.001 (Assymp.Sig.2-sided) where it’s smaller than 0.05. It means there is relationship significantly between demographic factors and reasons for quitting the job in hotel industry in China